2022
DOI: 10.22515/shirkah.v7i1.451
|View full text |Cite
|
Sign up to set email alerts
|

Halal Marketplace: The Influence of Attitude, Subjective Norms, and Perceived Behavior Control on Purchase Intention of Muslim Consumers

Abstract: Halal is currently a global concept that is becoming more universally recognized. Strengthening the digital economy is advocated by the 2019–2024 Indonesian Islamic Economic Masterplan (MEKSI), whose primary target is the halal market. Drawing in this issue, this study scrutinizes the influence of attitude, subjective norms, and perceived behavior control on the purchase intention of Muslim consumers in the halal marketplace. This study involves the Muslim community in Semarang, Indonesia. Taking a sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
4
4
0
1
Order By: Relevance
“…The third hypothesis states that subjective norms have a positive and significant influence on the attitudes of Muslim consumers of generation Y and Z who consume halal cosmetic products in Indonesia. This result is in line with research by (Fuadi et al, 2022) revealed that subjective norms have a significant influence on attitudes which results in consumer buying interest in halal-certified products. The results of the fourth hypothesis show that there is a positive and significant relationship between consumers' attitudes towards halal cosmetic products and their intention to buy these products.…”
Section: Discussionsupporting
confidence: 91%
“…The third hypothesis states that subjective norms have a positive and significant influence on the attitudes of Muslim consumers of generation Y and Z who consume halal cosmetic products in Indonesia. This result is in line with research by (Fuadi et al, 2022) revealed that subjective norms have a significant influence on attitudes which results in consumer buying interest in halal-certified products. The results of the fourth hypothesis show that there is a positive and significant relationship between consumers' attitudes towards halal cosmetic products and their intention to buy these products.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Muslims in Malaysia, who predominantly have a collectivist culture, show great loyalty and cohesion towards their circles, which is important. This supports the study of Ali et al (2020), Ali et al (2018), andFuadi et al (2022), but contradicts the findings of Jang and Cho (2022), Kasri et al (2023), Azam (2016), andZayed et al (2022), who found that subjective norms are not an important predictor of intention to purchase halal food.…”
Section: Discussionsupporting
confidence: 58%
“…In halal food research, a plethora of studies have examined the association between attitude and intention (Ali et al, 2018;Ali et al, 2020;Nursalwani & Zulariff, 2017;Sari et al, 2022). Although there is ample evidence that attitude is the best predictor of intention (Ali et al, 2020;Fuadi et al, 2022;Nursalwani & Zulariff, 2017;Sari et al, 2022), however, Ali et al (2018), Aslan (2023), andHarun et al (2023) found that attitude did not predict intention in their study. Thus, due to the contradictory results, the impact of attitude on purchase intention should be further investigated.…”
Section: Attitudementioning
confidence: 78%
See 1 more Smart Citation
“…Semakin tinggi pengaruh kelompok referensi terhadap makanan halal, maka semakin tinggi pula minat pembelian makanan halal. Penelitian tersebut didukung olehFuadi et al (2022) yang menemukan bahwa norma subjektif menunjukkan pengaruh yang signifikan terhadap niat beli konsumen muslim di marketplace halal. Dalam konteks pariwisata halal,Ramadhani et al (2020) mendapati bahwa norma subjektif berpengaruh positif dan signifikan terhadap niat untuk berkunjung ke wisata halal di Lombok.…”
unclassified